Changes of parameters of the heating period on the territory of Ukraine as a result of global warming - Lyalko, V.I.; Elistratova, L.A.; Apostolov, A.A. (Reports of the National Academy of Sciences of Ukraine, 2016)
The main climatic characteristics (beginning, end, duration) of the heating period on the territory of Ukraine are considered. Their changes under conditions of the modern climate are shown. The structure of the temperature regime of the heating period is revealed. The importance of the climatological characteristic of the heating period for the solution of questions of the rational use of the fuel power complex and its adaptation to its changes of the climatic conditions is emphasized.